Does Financial Sector Development Enhance the Relationship between FDI and Economic Growth? A Comparative Study of East African Countries - Kelly, Roger (Journal of Reviews on Global Economics, 2016)
This study examines the causal relationship between FDI and GDP growth in a number of East African countries, focusing on the impact of financial sector development on this relationship. There are strong theoretical reasons to believe that a developed financial sector will enhance the impact of FDI on growth, but empirical evidence remains scant. This study looks first at the short term causal relationship between FDI and GDP growth, using a robust methodology that avoids issues associated with Granger causality testing. This testing indicates little evidence of a relationship. Johansen cointegration testing yields little evidence of a long run relationship when a VECM containing just FDI and GDP growth is estimated, however once variables proxying financial sector development and an interaction variable between FDI and financial sector development are included, we find that although FDI and GDP growth may not be cointegrated directly, there is a relationship running through their interaction with the financial sector, and that FDI only appears to have a positive impact on GDP growth in cases where the financial sector is more developed. This finding is in line with the findings of previous researchers, and has important policy implications.